Eksplorasi Media dalam Pembelajaran Matematika Daring di Madrasah Ibtidaiyah - Hanin Nur Laili; Safarinda Tri Handayani; Sumbaji Putranto (UNION : Jurnal Ilmiah Pendidikan Matematika, 2021)
The learning media was selected by elementary school teachers in online learning was one that students access easily. Some elementary school teachers used WhatsApp in online learning. But it turns out there were some students who were having trouble accessing WhatssApp. The purpose of this study was to describe the learning media was chosen by teacher in online learning mathematics activities of 2nd grade students MI Tahfidz El Muna Q. The design of this study was a qualitative. The study population was a mathematics teacher of 2nd grade at MI Tahfidz El Muna Q. The data collection technique was carried out through observation and interviews. The result showed that the learning media was chosen by the teacher were using the application WhatsApp, with the features video, voice note, and video call.